Alpha Tocopherol-Induced Modulations in the Morphophysiological Attributes of Okra Under Saline Conditions - Naqve, Maria; Wang, Xiukang; Shahbaz, Muhammad; Mahmood, Athar; Bibi, Safura; Fiaz, Sajid (Frontiers in Plant Science, 2021)
Foliar spray of antioxidants is a pragmatic approach to combat various effects of salinity stress in agricultural crops. A pot trial was conducted to examine the effect of exogenously applied α-tocopherol (α-Toc) as foliar spray to induce morpho-physiological modulations in two varieties (Noori and Sabzpari) of okra grown under salt stress conditions (0 mM and 100 mM NaCl). After 36 days of salinity treatments, four levels (0, 100, 200 and 300 mg L–1) of α-tocopherol were sprayed. Salt stress significantly reduced root and shoot fresh and dry biomass, photosynthesis rate (A), transpiration rate (E), water use efficiency (A/E), stomatal conductance, internal CO2 concentration (Ci)and Ci/Ca), and photosynthetic pigments. Foliar spray of α-tocopherol proved effective in improving the growth of okra by significantly enhancing root dry weight, root length, shoot fresh weight, shoot length, Chl. a, Chl. b, Total chl., β-Car., Total Car., A, E, A/E, Ci, and Ci/Ca, leaf and root Ca2+ and K+ ion content, total soluble sugars, non-reducing sugars and total soluble protein content by significantly reducing root Na+ ion content. The Okra variety Noori performed better than Sabzpari in the examined attributes, and 300 mg L–1 application of α-tocopherol was more pronounced in improving the growth of okra by alleviating salinity effects. Therefore, the use of α-tocopherol (300 mg L–1) as a foliar spray is recommended to improve okra production in saline soils.